PENGUJIAN TECHNOLOGY ACCEPTANCE MODEL 2 TERHADAP MINAT WAJIB PAJAK DALAM MENGGUNAKAN E-SAMSAT - Kadek Indah Lestari; I Nyoman Putra Yasa; Putu Yunartha Pradnyana Putra (Jurnal Widya Akuntansi dan Keuangan, 2025)
This research using quantitative methods is basically aimed at finding out a number of factors that influence interest in using a technology system in the form of e-SAMSAT. These factors were studied using the Technology Acceptance Model approach with three types of variables, namely perceived usefulness, perceived ease of use, and social influence. The population in this research refers to motor vehicle taxpayers in Buleleng Regency. The sampling technique used was purposive sampling with sample size determination using G*Power software so that 119 respondents were obtained. The data collection method was carried out by distributing questionnaires. On the other hand, multiple linear analysis is used as a data analysis technique. This research proven that: (1) Perceptions of usefulness have a positive and significant influence on interest in using e-SAMSAT; (2) Perceptions of ease of use have a positive and significant influence on interest in using e-SAMSAT; and (3) Social influence does not have an impact on interest in using e-SAMSAT.